ANALISIS KELAYAKAN PRODUKSI BUBUK KAKAO SISTEM VACUUM ROASTING DAN LEMAK KAKAO SKALA INDUSTRI KECIL - Muh Syukri Sadimantara; Tamrin -; Nur Asyik (Agriplus, 2014)
Cocoa is an important ingredient in a variety of food and beverage industry and the mainstay of agricultural commodities with an important role in the Indonesian economy. Improving the quality of products processed cocoa powder and cocoa butter especially important in order to create superior products and win market. This can be achieved either by roasting vaccum system that is able to increase the levels of antioxidants in cocoa powder. In research conducted technical analysis of financial feasibility medium industrial vacuum systems roasting cocoa powder and cocoa butter in North Kolaka . Result of  the analysis of the technical aspects, the product obtained planned capacity of 5 tons of cocoa powder and cocoa butter 4.6 tons a year. For the necessary raw materials fermented cocoa beans were 12.4 tons/year. Machines used, among others, roaster machine, desheller, pemasta machine, the type of hydrolic press  cocoa, cocoa (panmill) and screening machines. The total capital investment of Rp.690.859.730, total production cost     Rp. 476.676.567 while proceeds from powder and cocoa butter are Rp.949.949.544. The calculation of eligibility criteria Net B/C of 2.05 was obtained. Rp.1.418.869.949 NPV, IRR 43.1%, BEP achieved at the production level of 1.3 tonnes and 1.1 tonnes of cocoa powder cocoa butter, and the payback period is 2 years and 7 months. The eligibility criteria of the calculation shows that the establishment of agro-industry units powder and cocoa butter in North Kolaka decent realized. Keywords: powder and cocoa butter, vacuum roasting, technical and financial analysis